Lipid and phospholipid composition of the inner mitochondrial membrane of hepatocytes under conditions of glutamate-induced steatohepatosis and correction with nanocrystalline cerium dioxide - M. M. Kondro; B. M. Verveha; T. V. Beregova; M. Y. Spivak; B. V. Gutyj (Regulatory Mechanisms in Biosystems, 2025)
The problem of studying the mechanisms of steatohepatosis development and its correction remains relevant, despite the significant number of scientific studies on the pathogenesis of metabolic-associated fatty liver disease. This is confirmed by the increase in morbidity, which may be associated with a wide range of factors that cause liver steatosis and the lack of effective therapeutic and preventive agents. The study aims to establish the lipid and phospholipid composition of the inner mitochondrial membrane of rat hepatocytes under conditions of diet- and glutamate-induced steatohepatosis and to evaluate the corrective effect of nanocrystalline cerium dioxide on the formation of steatohepatosis induced by neonatal administration of monosodium glutamate. The direction of the experiments included the study of the mechanisms of development of diet- and glutamate-induced visceral obesity in 4-month-old rats and the determination of the lipid and phospholipid composition of the inner membrane of hepatocyte mitochondria in rats under conditions of high-calorie diet and after neonatal administration of monosodium glutamate against the background of periodic administration of nanocrystalline cerium dioxide. It was established that rats that were on a high-calorie diet with a high content of fats, carbohydrates, and a reduced content of proteins for 4 months, and rats that were administered monosodium glutamate in the neonatal period, develop ed visceral obesity without the manifestation of hyperphagia, characterized by dyslipidemia and the development of steatohepatosis. A feature of the development of diet- and glutamate-induced steatohepatosis is mitochondrial dysfunction, which is characterized by changes in the lipid and phospholipid composition of the inner membrane of hepatocyte mitochondria. Not only structural changes occur in the membrane, but also dysfunctional changes in the mitochondria as a whole, manifesting themselves in the fact that ROS are generated in the respiratory chain instead of ATP, and this causes the development of oxidative stress in both the mitochondria and the entire hepatocyte. Periodic administration of nanocrystalline cerium dioxide to rats with glutamate-induced steatohepatosis significantly restore d the lipid and phosph o lipid composition of the inner membrane of hepatocyte mitochondria, reduce d manifestations of oxidative stress, and reduce d the content of oxidized forms of phosphatidylcholine and phosphatidylethanolamine in the inner membrane of hepatocyte mitochondria against the background of normalization of cardiolipin content, which indicates the antioxidant effect of this drug and the possibility of its use for the prevention of steatohepatosis.